SPORTS AND EMBODIMENT - Leoni, Mariano Gonzalez (2018)
The theory of embodied cognition implies that cognitive processes depend fundamentally on the physical characteristics of the subject’s body. If this is true, physical aspects of an individual play a significant role in its cognitive process, and because of that, the theory rivals with all perspectives that defend any kind of duality, separating body from mind, such as the Cartesian thesis. This article presents the embodiment thesis, its main ideas, and provides examples within sports that support its validity. To do so, ideas from contemporary authors of various fields are presented and used to understand certain realities and situations that have gained importance in today’s world, one in which sports has become one of the most significant manifestations of human culture. Concepts like “cognitive delegates”, “a-rational” performances and the two-system cognitive hypothesis will be introduced to illustrate the relevance of the embodiment thesis in relation to all human activity.